2-Segal sets and the Waldhausen construction - Bergner, J; Osorno, A; Ozornova, V; Rovelli, M; Scheimbauer, C (Elsevier, 2017)
It is known by results of Dyckerhoff–Kapranov and of Gálvez-Carrillo–Kock–Tonks that the output of the Waldhausen S • -construction has a unital 2-Segal structure. Here, we prove that a certain S • -functor defines an equivalence between the category of augmented stable double categories and the category of unital 2-Segal sets. The inverse equivalence is described explicitly by a path construction. We illustrate the equivalence for the known examples of partial monoids, cobordism categories with genus constraints and graph coalgebras.